Prevalence of Habit Disorders In Children: An Experience From A Tertiary Care Hospital - Khursheed, Muhammad Hamza; Rasheed, Javaria; Sheikh, Muhammad Aslam; Ali, Perwez (Journal of Rawalpindi Medical College, 2026)
Objective: The study aimed to determine the prevalence of habit disorders in children visiting the paediatric outpatient department of a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the Pediatric Medicine Department of the CH & ICH Multanfrom 24th June to 23rd September 2025. Two hundred children aged 1 to 12 years, of either gender, attending the outpatient department were consecutively enrolled after informed parental consent. Children with neurological and psychiatric disorders (e.g., autism spectrum disorder, ADHD, mental retardation, cerebral palsy, epilepsy) were excluded. Demographic data were recorded, and parents were asked about habit disorders: thumb sucking, nail biting, bruxism, and hair pulling. Data was analyzed using SPSS version 25. Descriptive statistics in the form of mean ± SD for numerical data and frequency percentages for categorical data are described. Results: The mean age was 4.8 ± 2.2 years, and 67.5% were males. Lack of maternal formal education in 53% of the cases, and 32.5% had a positive family history of habit disorders. Most children belonged to lower-middle socioeconomic status (72%). Habit disorders were identified in 30% of the children. Bruxism was most common (11.5%), followed by thumb sucking (7.5%). Habit disorders were significantly more common in children ≥ 5-years of age in contrast to < 5-years of age (38.1% vs. 22.3%, p-value 0.015). Conclusion: Habit disorders affect nearly 1/3 of the children in this population, with bruxism most common. Screening during routine periodic visits may facilitate early identification and parental counseling. Key Words: Behaviour, Bruxism, Habits, Children